PERSEPSI GURU SWASTA TENTANG AKREDITASI DAN DINAMIKA IKLIM SEKOLAH PASCA PUTUSAN MAHKAMAH KONSTITUSI REPUBLIK INDONESIA NO: 3/PUU-XXIII/2025 - Hariyadi, Bachtiar (Jurnal Manajemen Pendidikan, 2025)
School climate plays a crucial role in determining educational effectiveness. School climate encompasses interactions between teachers, students, and management, as well as a work environment that supports learning. The Constitutional Court Ruling No: 3/PUU-XXIII/2025 mandates the government to ensure free compulsory education for all primary education institutions, including private schools, presenting both challenges and opportunities for accreditation and school climate. This study aims to understand private school teachers’ perceptions of accreditation and school climate dynamics following the ruling. Using a qualitative approach, data were collected through semi-structured interviews and non-participant observations from 20 teachers in five private primary schools in East Java. Thematic analysis revealed that 70% of teachers view accreditation as a tool for quality improvement, while 25% feel burdened by administrative demands. School climate showed increased teacher collaboration (80%), but tensions with management arose due to funding uncertainties. Parental expectations for educational quality also rose. The ruling offers opportunities for government support, but funding and administrative challenges must be addressed. The study recommends clear funding guidelines and teacher training to support private schools.